Esquema para un programa de desarrollo campesino en la sierra del Perú - Figueroa, Adolfo (1984)
Poverty in Peru is concentrated in the countryside. Peasant families, smallholder farmers who produce on small plots, make up about 30% of the country's population and are at the bottom of the income pyramid. There is no larger or poorer social group in Peru than the peasantry. With the economic crisis of recent years, urban poverty has become more acute; but even so, families with the greatest deficits in the satisfaction of today's human needs are still found in rural areas (Figueroa, 1982). Resolving the economic inequality, the social abyss, and the social discrimination that characterizes Peruvian society requires, first of all, improving the real income of peasants. Based on the results of my research for several years, I would like to present in a schematic way the economic policy alternatives to reach this objective.